2015
DOI: 10.1521/pedi_2014_28_148
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of the Dutch Version of the McLean Screening Instrument for BPD (MSI-BPD)

Abstract: Borderline personality disorder (BPD) often goes unrecognized, and therefore a short but accurate screening tool is desired. The present study investigated the psychometric properties of the 10-item McLean Screening Instrument for BPD (MSI-BPD) in 159 well-diagnosed female participants. The MSI-BPD showed excellent internal consistency (α = .90). When compared to BPD diagnoses based on a structured clinical interview (SCID-II), the MSI-BPD showed substantial congruent validity (receiver operating characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…We found that the MSI-BPD demonstrated high diagnostic efficiency (ROC = 0.93), with a cut-off of 5 showing a good correlation with the SIDP IV (sensitivity = 0.87; specificity = 0.85). The optimal cut-off is below the initially defined threshold of 7 [5], and the score of 5 was also found in the study by van Alebeek and colleagues [14] in a sample of adolescents and young adults in psychiatric care and in the study by Andre and colleagues [16] in a sample of adult psychiatric in-and out-patients.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…We found that the MSI-BPD demonstrated high diagnostic efficiency (ROC = 0.93), with a cut-off of 5 showing a good correlation with the SIDP IV (sensitivity = 0.87; specificity = 0.85). The optimal cut-off is below the initially defined threshold of 7 [5], and the score of 5 was also found in the study by van Alebeek and colleagues [14] in a sample of adolescents and young adults in psychiatric care and in the study by Andre and colleagues [16] in a sample of adult psychiatric in-and out-patients.…”
Section: Discussionsupporting
confidence: 52%
“…The recent literature review by Zimmerman and Balling [11] reports 12 studies of the MSI-BPD, including 3 studies in adolescent and young adult populations [12][13][14]. The sensibility of the scale ranged from 48.4% [12] to 91% [15] and the specificity of the scale ranged from 19.2% [15] to 90.2% [16]. A maximization approach to select an optimal cut-off (the best balance between sensitivity and specificity) was widely used and the authors recommended cut-offs ranging from 5 [12] to 8 [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The McLean Screening Instrument for Borderline Personality Disorder (MSI-BPD) is a brief, 10 item, self-report questionnaire used to measure BPD symptoms (Zanarini et al, 2003; scale range 0-10). For the Dutch version, adequate internal consistency, high specificity and sensitivity, and a high test-retest correlation after four months were found (André, Verschuere, & Lobbestael, 2015;Verschuere & Tibboel, 2011). In the current sample, internal consistency was good (α = .87).…”
Section: Bpd Traitsmentioning
confidence: 93%